Modeling of the Management System for the Small Hotels Construction - Shchepak, Vira; Senenko, Natalia; Senenko, Inna (International Journal of Engineering and Technology, 2018)
The aim of the work was to investigate the aspects of construction, simulate the management system for the construction of small hotels with the development of the graph model, determine the main characteristics of the system components and perform their evaluation using the integrated assessment technique.A systematic approach was used in the process of preparing the publication.The study has determined that the construction of hotels is formed under the influence of a significant number of different factors of the external and internal environment and is a complex process. It is proposed to consider the construction of small hotels in conjunction with the financing, design, development of recreational areas and profitability of the future hotel business.The construction management system is also complex and complicated. For the effective functioning of such a system, the integration of its components on the basis of modeling was carried out. For this purpose, graph theory has been used and a graph-model of the control system has been developed. This approach made it possible to simplify the management system for the construction of small hotels and to distinguish two main subsystems: engineering-construction and economics. The first subsystem includes building objects and recreational areas, the second - investor-customers.The components and functions of the model have been described. The basic characteristics of subsystems and their interrelations were singled out. Then an example of an assessment of the main characteristics of the engineering and construction subsystem using the integrated assessment technique was given.As a result, the most effective variant of the formation of the engineering and construction component of the management system for the construction of small hotels has been determined.Prospects for further research are an in-depth study of the interrelationships between the components of the management system for construction of small hotels and formation of the development direction for this system.Â Â